Developing a STEM-integrated project-based hybrid learning design for statistics education and prophetic character - Anwar, Rahmad Bustanul; Rahmawati, Dwi; Rosa, Friska Octavia (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to develop a STEM-integrated project-based hybrid learning design for the mathematical statistics to enhance students’ prophetic character and improve their conceptual understanding of statistical concepts. The research addresses the need for innovative instructional designs that simultaneously support cognitive achievement and character development in higher education hybrid learning environments.Method: The research employed a Research and Development (R&D) approach following the Plomp model, which includes preliminary research, prototyping, assessment, and implementation phases. Validation was conducted by content, instructional design, and digital technology experts, while practicality was assessed through a small-group trial. Effectiveness was evaluated using pretest-posttest instruments and prophetic character questionnaires administered to 20 students enrolled in the course. Data were analyzed using normalized gain (N-Gain) and descriptive statistics to determine improvements in cognitive and character outcomes.Findings: The learning design achieved high validity (84.67%) and very high practicality (87.5%), demonstrating feasibility for implementation. Implementation results indicated that students’ problem-solving skills showed the highest improvement (N-Gain = 0.75, high), while communication (0.64) and collaboration (0.58) skills improved moderately. Students’ conceptual understanding of statistics improved moderately (average N-Gain = 0.52), with the majority achieving moderate improvement. These findings confirm that the hybrid STEM-PjBL design effectively promotes both cognitive and prophetic character development.Significance: The study provides a validated and practical instructional model that integrates STEM, project-based learning, and hybrid learning principles to foster students’ cognitive skills and character values. This design offers a replicable framework for instructors to implement authentic, engaging, and value-oriented learning in higher education, contributing to both theoretical and practical advancements in hybrid STEM education.